Advancing TOEFL Proficiency among Darussalam International High School Students: Community Service Research - Farida, Farida; Z, Edy Murdani; Rahman, Nur Fuadi; Hikmah, Nur; Yudaningrum, Sitra; Clevara, Yayas (SIMAS: Jurnal Pengabdian Masyarakat, 2025)
This study explores a community-based TOEFL preparation program for secondary students at an international school in Samarinda, East Kalimantan an underrepresented context in current research. Departing from conventional test-focused instruction, the program emphasized student autonomy, project-based learning, and reflective practices within a non-formal educational framework. Using a qualitative approach, the study involved 18 students from Grades 11 and 12 to explore their experiences and engagement in language learning. Rather than merely tracking score improvements, the research focused on how students interacted with collaborative and contextual learning strategies. Results showed that most participants reached Good to Very Good proficiency in Listening (83.33%), Structure and Written Expression (72.23%), and Reading Comprehension (66.67%). The program not only improved academic English skills but also enhanced motivation, confidence, and active participation. This study offers an innovative, student-centered model for TOEFL preparation, valuable for educators and practitioners working in similar educational and community settings.